INSTAGRAM CONTENT MARKETING ANALYSIS IN INCREASING UMRAH INTEREST (STUDY ON JANNAH TRAVEL ACCOUNT) - Sieradianto, Dinda Ayu; Ardiansyah, Angga; Muttaqin, Rahmat Bahaul (Multazam : Jurnal Manajemen Haji dan Umrah, 2024)
One marketing strategy adopted by umrah travel companies is using content on the Instagram platform. This is in response to the increasing business competition in the umrah industry, where the growing number of umrah agencies adds complexity to the market. The success of companies in winning this competition heavily relies on their ability to reach and influence the public widely through effective information dissemination. The theory used in this research is the theory of the 4 Pillars of Social Media Strategy. Data collection techniques through observation and documentation studies involve systematic and planned recording of events or phenomena. The type of observation applied in this research is non-participatory observation, which means it does not involve direct participation. Data collection techniques through documentation studies. The conclusion drawn is that the information and education content posted by the Instagram account @JannahTravel perform well, marked by a large number of likes. This practically implies as an evaluation tool and advice in creating content plans, by increasing the proportion of information and education content to enhance the interest of potential umrah pilgrims who are the audience.